In-silico approach for the identification of mirror repeats within Glucagon, Sox17, Gapdh and PKLR diabetic genes of Rattus norvegicus - Babli,; Kumar, Parveen (International Journal of Applied Sciences and Biotechnology, 2026)
Repetitive sequences are immensely distributed in the genomes of all viruses, bacteria, plants and animals. Repetitive sequences throughout the genome in both coding and non-coding regions are a major source of endogenous DNA damage, due to the propensity of many of them to form alternative non-B DNA structures that can interfere with replication, transcription and DNA repair The alternative non-canonical  structures include triple-helices, hairpins, cruciforms and slipped structures and they are more likely to form at particular repetitive sequences such as mirror repeats, inverted repeats, direct repeats, and short tandem repeats. Although mirror DNA repeats were discovered in genomic DNA,the ability of a subset of lengthy homopurine-homopyrimidine mirror repetitions (H-motifs) to form a triple-helical DNA secondary structure was the only functional property that was thoroughly identified. Over the past decade, biological databases have expanded significantly due to developments in genomics, computational biology, and bioinformatics. A computational method was used in this study to identify mirror repetitions in the Rattus norvegicus’s diabetic genes. The Fast Parallel Complement Blast (FPCB) tool, a rapid and efficient bioinformatics method for identifying gene and genome repeats, was used to do this.  Mirror repeats were found 199 in Glucagon, 135 in Sox17, 116 in Gapdh and 167 in PKLR genes during this study. Through this study, we can better understand the function of mirror repeats in the Rattus norvegicus’s genes, which may be further linked to mirror repeats in the human genome.Int. J. Appl. Sci. Biotechnol. Vol 14(1): 28-43.